PEWARISAN SIFAT KETAHANAN TANAMAN MELON (Cucumis me/o L.) TERHADAP POWDERY MILDEW (Podosphaera xanthii (Castag.) Braun et Shishkoff) = INHERITANCE OF RESISTANCE TO POWDERY MILDEW Podosphaera xanthii (Castag.) Braun et Sh - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Powdery mildew is afungal disease that causes subtantiallosses in melon production around the world including Indonesia. Resistant melon cultivar to powdery mildew is important to increase melon production. Hence, the objectives of this study were to study melon resistance against powdery mildew and its inheritance. A F2 population was obtained from self pollination between FI &#9792